PCS-14 Potential Reproductive Adaptation of Mice (Mus musculus) from Mild Stress using Dark Light Cycle Alteration - D N Pristihadi; M Fakhrudin; N M D Haq; A Boediono (Hemera Zoa, 2018)
Stress regarded as a major cause of body destruction. Stress can trigger the gluconeogenesis mechanism that initiates new glucose production from another molecule in the body’s storage tissue depot. When the stress occurs, the body gives a ‘fight or flight’ response. In this condition, the body prioritizes to survive rather than multiplying itself. The reproductive system categorized as the highest rank in the body needs pyramid. Therefore, the reproductive system is on the first line to be sacrificed when the stress occurs.This research was conducted to observe the potential mice's reproductive adaptation from mild stress using dark light cycle alteration. Mice considered as the small laboratory animal with rapid metabolism rate. This study expected to be able to enrich the information of mice’s biology reproductive adaptation.